Rheological behavior of plant-based beverages - Silva, Kamilla [UNESP]; Machado, André; Cardoso, Cláudio; Silva, Flávio; Freitas, Fernanda (My University, 2020)
The aim of this research was to study the rheological behavior of a plant-based beverage made of Brazil nut (Bertholletia excelsa) and Baru (Dipteryx alata Vogel) and a nut-based beverage made of Brazil nut (Bertholletia excelsa) and Macadamia (Macadamia integrifolia) at the temperatures of 25, 45 and 80 °C. Experimental data were adjusted to the models of Newton, Ostwald-de Waele, Herschel Bulkley and Bingham. The formulations of the beverages were obtained from a simplex-centroid design, based on the panelists acceptance in the sensorial evaluation. Rheological behavior showed no differences between the beverages and rheological data were best fit to Ostwald-de Waele model, at the three temperatures for both beverages, presenting a non-Newtonian behavior, with a pseudoplastic characteristic (n <1). In general, the nut-based beverage made of Brazil nut and Macadamia presented lower values than a plant-based beverage made of Brazil nut and Baru for an apparent viscosity, at the three temperatures, requiring less tension to flow.
Keywords: Baru; Brazil nut; Lactose free; Macadamia; Non-dairy milk